Ecological relationships between the armadillo lizard, Cordylus cataphractus, and the southern harvester termite, Microhodotermes viator - Shuttleworth, Cindy (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Botany and Zoology))--University of Stellenbosch, 2006.